Supporting the Development of Digitally Competent VET Teachers in Serbia and Russia - E. Burns; E. Silvennoinen; V. A. Kopnov; D. E. Shchipanova; N. Papić-Blagojević; S. Tomašević (Russian State Vocational Pedagogical University, 2020)
Introduction. In the modern educational space, an intensive digital transformation is currently taking place, which imposes new requirements for teacher competencies. This determines the relevance of setting goals and solving problems in order to develop up-to-date models for improving the qualifications of teachers of vocational education and training (VET). The paper discusses the current state of the development of digital competencies of teachers and teachers of Serbia and Russia in line with the European Digital Competence Framework (DigComp) and the European Digital Competence Framework for Educators (DigСompЕdu). The paper includes an analysis of the peculiarities of vocational education and training systems, as well as the directions of further training of teachers, conducted by participants in the international project "Professional Development of Vocation Education Teachers with European Practices (Pro-VET)". In order to better understand national contexts, the content of the reports of the participating countries of the project was analysed in the context of the EU policy and strategy for the development of digital competency of VET teachers. In this article, the authors focus on exploring digital competencies required of VET teachers within the European Digital Competence Framework for Educators (DigСompЕdu) to identify digital competencies and development needs of Serbian and Russian VET teachers when working in online learning environments. The aims of the research are the following: 1) to compare the educational needs of Russian and Serbian VET teachers in the development of their digital pedagogical competencies; 2) to identify the theoretical and practical base for VET teachers' digitally competent development programme design in the context of online learning according to the best European practices in the field of VET. Methodology and research methods. The development of the model was based on learning theories, didactics and practical approaches to soft skills development in online learning environments. The research has been conducted by the means of document analysis, theoretical analysis and synthesis methods, comparative method, modelling method and expert estimation method. Results and scientific novelty. Key aspects of VET teacher training systems in Russia and Serbia are compared and needs in development of digital pedagogical skills of Russian and Serbian VET teachers are identified. A developed model of VET teachers' digitally competent development programme design in the context of online learning according to best European practices in this fields is represented by two components: structural and functional. The structural component of VET teachers' digitally competent development model contains: learning theories and didactics, adult learning theories, soft skills development approaches in online learning, learning outcomes development approaches. The functional component of the model contains: national and European educational policy, strategies in the field of digitalisation of education and the development of digital competencies of teachers, European Union policies related to online learning; pedagogical, psychological and didactical design parameters of the content of advanced training programmes in the context of e-learning. Practical significance. The demonstrated model is being tested in the framework of the implementation of the international Pro-VET project supported by ERASMUS+. Methodological approaches, procedure and tools of VET teachers' digitally competent development are being developed and tested. The application of digitally competent development programmes ensures the transparency of training and allows for the correlation of national and international training programmes as well as the development of academic and professional mobility of VET teachers. The process of designing such educational training programmes in online environment for VET teachers has begun at some universities in Russia and Serbia (participants of the project). The developed online training programmes can be used as a basis to design more quality online courses beyond the Pro-VET project in the sphere of professional development for VET teachers.